Community Characteristics and Readmissions: Hospitals in Jeopardy - Michele L. Summers; Serdar Atav (Rural Nurse Organization; Binghamton University, 2021)
Objective: The purpose was to identify community characteristics that contribute to reductions in readmission rates and reimbursement penalties for hospital systems in upstate New York. Methods: Hospitals in upstate NY were selected (N = 94). Using an ex post facto design and the ecological model, community characteristics of hospital systems were analyzed and coded. Independent t-tests, ANOVA, and Pearson Correlation tests were conducted. Results: Characteristicscorrelated with reduced hospital readmission rates and reimbursement penalties included hospitals (1) with critical access status; (2) located in counties with a better county health rank; and (3) located in a primary care shortage area that utilized house calls. Discussion: Implications include supporting policies that increase access to services, improve formulas for reimbursement, and encourage innovation in care delivery models. Future research efforts should focus on house calls in primary care shortage areas. Keywords: readmission rates, ecological model, house calls, community health DOI: https://doi.org/10.14574/ojrnhc.v21i1.638